2020
DOI: 10.1097/mjt.0000000000000786
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bisoprolol on the Level of Dabigatran

Abstract: This study demonstrated the interaction between dabigatran and bisoprolol, which is modulated with dabigatran dosage and concomitant treatment with proton-pump inhibitor and digoxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Baseline dabigatran plasma levels and plasma levels at 2 h following drug administration were found to be significantly higher in patients on concomitant bisoprolol (group 1) as compared to those not on bisoprolol (baseline: 161.35 ± 95.81 vs 87.94 ± 51.77 ng/mL; after 2 h: 236.87 ± 119.69 vs 151.00 ± 68.88 ng/mL). The authors concluded that an interaction between bisoprolol and dabigatran exists, and while there are no associations made between the increase in plasma drug concentrations and outcomes, this study supports further research to better define the impact these interactions have on clinical outcomes ( Nehaj et al, 2020 ) [c].…”
Section: Bisoprololmentioning
confidence: 58%
“…Baseline dabigatran plasma levels and plasma levels at 2 h following drug administration were found to be significantly higher in patients on concomitant bisoprolol (group 1) as compared to those not on bisoprolol (baseline: 161.35 ± 95.81 vs 87.94 ± 51.77 ng/mL; after 2 h: 236.87 ± 119.69 vs 151.00 ± 68.88 ng/mL). The authors concluded that an interaction between bisoprolol and dabigatran exists, and while there are no associations made between the increase in plasma drug concentrations and outcomes, this study supports further research to better define the impact these interactions have on clinical outcomes ( Nehaj et al, 2020 ) [c].…”
Section: Bisoprololmentioning
confidence: 58%
“…22,25,26 Although there are differences between these 2 assays, the measurement outcomes are not so different, as 20% difference is negligible from a clinical perspective. A total of 5 dabigatran-drug interaction studies [72][73][74][75][76] were identified from the search but excluded from the meta-analysis as they may affect the estimated pooled concentrations. The use of concomitant proton-pump inhibitor with dabigatran was observed in 3 studies and found to significantly decrease dabigatran concentration.…”
Section: Discussionmentioning
confidence: 99%
“…74,76 Dabigatran etexilate is a substrate of P-gp transporter, and concomitant administration of P-gp inhibitor can increase the bioavailability of dabigatran, therefore resulting in higher dabigatran concentration. 74,76 There are some limitations in this study. Seven articles were excluded from the systematic review as they were not in English.…”
Section: Discussionmentioning
confidence: 99%
“…This does not exclude that, in the context of polytherapy, other drugs may, in some way, have altered the absorption or metabolism of apixaban, considering the patient was taking bisoprolol, zofenopril, amlodipine, and furosemide for hypertension and lansoprazole for gastric protection. In the literature, there are some hints regarding bisoprolol and P-gp, and at least one evidence of interaction with dabigatran, although with contrasting evidence [ 47 , 48 , 49 , 50 , 51 , 52 ]. Therefore, considering that dabigatran itself is a substrate of P-gp, a further hypothesis is that a specific interaction regarding amlodipine, bisoprolol, or other drugs prescribed may have selectively altered the absorption (or excretion) of apixaban.…”
Section: Discussionmentioning
confidence: 99%